2010
DOI: 10.1111/j.1473-2165.2010.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Original Contribution: Hyperandrogenism does not predispose patients to photoepilatory treatment failure: a single‐center review

Abstract: Studies have suggested that patients with PCOS tend to be more treatment resistant to light-mediated depilation compared with their non-PCOS counterparts. We conducted a retrospective assessment of 29 hirsute patients treated between January 2006 and February 2007 to assess whether those with unsatisfactory hair clearance after treatment with intense pulsed light (IPL) were predominantly hyperandrogenic. The number of IPL sessions was also recorded for those patients failing to improve on treatment. Seventy-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
2
0
1
Order By: Relevance
“…There was no difference in hair reduction between PCOD patients and non PCOD patients in this study which is also supported by Taylor et al 15 …”
Section: Efficacy In Pcod and Nonpcod Groupssupporting
confidence: 89%
“…There was no difference in hair reduction between PCOD patients and non PCOD patients in this study which is also supported by Taylor et al 15 …”
Section: Efficacy In Pcod and Nonpcod Groupssupporting
confidence: 89%
“…But it is so higher in Iraqi ladies where the facial hirsutism affects 26.8% of them [13]. The response to IPL treatment for facial hirsutism varies from 10 to 88.66% among various researchers [1,6,11,12,[14][15][16][17][18][19][20][21]. The current study showed that 62.9% had good and 25.8% excellent hair reduction rate.…”
Section: Discussionmentioning
confidence: 69%
“…Khodaeyani et al found no statistically significant difference between the IPL response and body site [19]. Taylor et al study showed that there was no statistical difference between the IPL treatment response and patients with a history of PCOD [16]. The current study showed that IPL treatment was not statistically significant difference with the age of the patient, facial anatomical location, and skin type, while the study found a highly significant difference in relation to the patient with a history of PCOD and patient satisfaction.…”
Section: Discussionmentioning
confidence: 97%
“…de 88 mujeres con hirsutismo facial sometidas a Láser Alexandrita, en sesiones cada 4-6 semanas, mostró una reducción de la severidad del hirsutismo luego de 6 meses de tratamiento, una disminución del tiempo de remoción del vello de 112 a 21 minutos semanales, así como una disminución de los síntomas ansiosos y depresivos 33 . Si bien no existen estudios disponibles, se ha postulado que el uso de depilación láser junto con agentes hormonales puede optimizar la depilación prolongada por láser previniendo la transformación a pelo terminal en pacientes con SOP, siendo necesarios más estudios que avalen estos resultados 34 .…”
Section: Manifestaciones Dermatológicasunclassified